Prostate-specific membrane antigen and its truncated form PSM' - Mlcochová, Petra; Barinka, Cyril; Tykvart, Jan; Sácha, Pavel; Konvalinka, Jan (The Prostate, 2009)
BACKGROUND: Prostate specific membrane antigen (PSMA) is a type II transmembrane protein overexpressed in prostate cancer as well as in the neovasculature of several non-prostatic solid tumors. In addition to full-length PSMA, several splice variants exist in prostatic tissue. Notably, the N-terminally truncated PSMA variant, termed PSM', is prevalent in healthy prostate, and the ratio of PSMA/PSM' mRNA has been shown to correlate with cancer progression. The widely accepted hypothesis is that the PSM' protein is a translation product arising from the alternatively spliced PSM' mRNA. METHODS: Differential ultracentrifugation, cell surface biotinylation, Western blotting, and enzyme activity measurement were used to study the origin and localization of the PSMA/PSM' variants in prostatic (LNCaP; lymph-node carcinoma of the prostate) and non-prostatic (HEK293) cell lines. These experiments were further complemented by analysis of the N-glycosylation patterns of the PSMA/PSM' proteins and by site-directed mutagenesis. RESULTS: We identified PSM' protein expression in both the LNCaP cell line and a non-cancerous HEK293 human cell line transfected with a plasmid encoding full-length PSMA. Differential centrifugation revealed that PSM' is localized predominantly to the cytosol of both these cell lines and is proteolytically active. Furthermore, the PSM' protein is N-glycosylated by a mixture of high-mannose and complex type oligosaccharides and therefore trafficked beyond the cis-Golgi compartment. CONCLUSIONS: Our data suggest that the PSM' protein is likely not generated by alternative splicing of the PSMA gene but by different mechanism, probably via an endoproteolytic cleavage of the full-length PSMA.
Keywords: Mitochondria; Prostatic Neoplasms; Adenocarcinoma; nádory prostaty; Lysosomes; Humans; místa sestřihu RNA; ledviny; mikrozomy; Kidney; Prostate-Specific Antigen; lidé; mitochondrie; Microsomes; buněčné linie; transfekce; glykosylace; Cell Line; Male; prostatický specifický antigen; nádorové buněčné linie; Transfection; lyzozomy; adenokarcinom; Cell Line, Tumor; mužské pohlaví; Glycosylation; RNA Splice Sites